Contradiction in the agrofinancial regulation of agricultural producers - Szilágyi, Bernadett (Acta Agraria Debreceniensis, 2009)
Hungary is a country of favourable conditions with agropotential, for this reason the regulations regarding agriculture is constantly the bone of legislative contention. Thepurpose of this study is to present the actual agropotential contradictions concerning the agricultural producers, specifically focusing on certain problems without any detailed representation of the valid rules of law. The agrofinancial anomalies referring to agricultural producers can be found mostly in the system of the personal income tax (allowance, tax immunity), the value added tax (special agricultural legal position) as well as the social insurance.The severity of the problem is supported by the agricultural producers’ behavioral types of paying taxes, globalisation process of these days and our place in the European Union. The resolution of the contradictions in agriculture does not lie by any means in the proper way of making the rules of the law of taxation, but in a comprehensive economic policy, which is to be waited for.